Modulation of Protein C Inhibitor Activity by Histidine-Rich Glycoprotein and Platelet Factor 4: Role of Zinc and Calcium Ions in the Heparin-Neutralizing Ability of Histidine-Rich Glycoprotein - Kazama, Yoshiaki; Koide, Takehiko (Thrombosis and Haemostasis, 1992)
Effects of zinc and calcium ions on the heparin-neutralizing abilities of histidine-rich glycoprotein (HRG) and platelet factor 4 (PF4) were examined. Both HRG and PF4 effectively neutralized the ability of heparin to accelerate the activated protein C (APC) and the thrombin inhibitions by protein C inhibitor (PCI). The heparin-neutralizing ability of HRG in the APC inhibition by PCI, however, was decreased in a Ca2+-dependent manner and apparently lost at 1 mM Ca2+, while it was enhanced by Zn2+ regardless of the presence or absence of Ca2+. The heparinneutralizing ability of HRG in the thrombin inhibition by PCI was not affected by Ca2+.In contrast to HRG, there was no significant difference in the heparin-neutralizing ability of PF4 in the presence or absence of 1 mM Ca2+. These results strongly suggest additional physiological functions of HRG and PF4 as modulators of PCI.